ACCESS TO INFORMATION AND UNDERSTANDING OF THE TEMBILAHAN COMMUNITY INSURTECH AS A DIGITAL FINANCIAL INNOVATION - SM Guntur; Qoriatul Fatmasari; Dandi Agustiyan (Indragiri Research Center (ingreat), 2025)
The development of financial technology (fintech) is driving the transformation of digital financial services, including in the insurance sector through insurance technology (insurtech). Insurtech is expected to increase public access to and understanding of digital-based insurance services. However, the level of public access to information and understanding ofinsurtechare still diverse, especially in non-metropolitan areas. This study aims to analyze access to information and the understanding of the Tembilahan community regarding insurtech as a digital financial innovation and identifying the factors influencing it. This study used a qualitative approach with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation of the purposively selected Tembilahan community. Data analysis was conducted using the Miles, Huberman, and Saldaña model. The results showed that the community obtained information insurtech through various channels, especially digital media and social communications, although the information received is not yet fully comprehensive. Public understanding of insurtech is still in its early stages and is influenced by digital literacy, financial literacy, perceived benefits, and the level of trust in digital financial services. This research emphasizes the importance of strengthening access to sustainable and contextual digital financial information and education to support public understanding of digital financial services insurtech.